When old and new media collide: The case of WikiLeaks. (June 2014) - Hindman, Elizabeth Blanks; Thomas, Ryan J
In November 2010, WikiLeaks released over a quarter of a million US State Department diplomatic cables to the world's media, exposing private communications between diplomatic officials at US embassies across the globe and the State Department at Washington, DC. This study analyzes the WikiLeaks controversy through institutional views of the US news media. Our analysis of 83 newspaper editorials found four prominent themes in US newspaper discourse: (1) The contrast between the "discretion and maturity" of traditional journalism and the rash actions of WikiLeaks; (2) The need for "old media" in a new media landscape; (3) The tension between the public's right to know and national security; and (4) The invocation of the Pentagon Papers as a way of drawing clear lines of difference between journalism's past and its possible future. Our findings indicate ongoing tension between "old" and "new" media at a time when definitions of journalism are increasingly diffuse.